(untitled) (City: History, Culture, Society, 2026)
This article presents a comprehensive study of the historical development of match production in the Volyn region, with a particular focus on the Rivne Match Factory. The research traces the evolution of the industry from artisanal to industrial-scale production, highlighting key technological innovations, including the introduction of safety (non-phosphorus) matches. The technological process is examined in detail, encompassing all stages from wood preparation to the application of the ignition compound and packaging of the final product. Special attention is given to the socio-economic impact of the factory on the local community, particularly the creation of employment opportunities for women and children in Rivne in the early 20th century. Based on archival sources, cartographic materials, and unique photographs taken during Semen An-sky’s 1912 ethnographic expedition, the study reconstructs the likely location of the factory and its operational characteristics. The article analyzes the reasons for the factory’s closure in 1922, including economic instability, the establishment of the Polish state match monopoly, and discriminatory policies against Jewish entrepreneurs. A separate section is devoted to the attempt to revive match production in the Rivne region in 1998, which led to the establishment of a modern factory in the town of Berezne. This study underscores the significance of the match industry as a driver of regional economic and social development and contributes to the preservation of historical memory regarding lesser-known aspects of local industrial heritage.